Behavioural profile of drug users attending public drug-treatment centres in Sicily: the role of social context (Italian Journal of Public Health, 2007)
Objective: Investigations of injecting drug users (IDUs) have suggested that the social context may influence high-risk behaviours in this population. The aim of this study was to describe knowledge, attitudes and behaviours of IDUs attending public drug-treatment centres in our area.Study design and methods: A cross-sectional survey was conducted between July 2002 and February 2004, enrolling 607 drug users attending four public drug-treatment centres in the Palermo area. Two of them were located inside the urban area, whereas the other two were in rural districts near the city. All participants answered an anonymous questionnaire concerning social and demographic characteristic and potential high-risk behaviours.Results: IDUs living in urban context have a higher educational level, higher number of sexual partners, as well as a lower prevalence of exchanging sex for drugs. Conversely, IDUs living in suburban/rural context are less likely to share syringes and more likely to have used light drugs in the past. Suburban/rural IDUs drink more alcohol but smoke less cigarettes/day, although both groups are strong smokers.Conclusions: The results suggest that public drug-treatment centres should take in consideration the adoption of specific programs targeting specific groups, in line with the profile and needs of the subjects in each context in order to promote approaches leading to risk reduction.
Keywords: Drug users; behaviour; social context; public drug-treatment centres; high risk behaviour